OPTIMALISASI HASIL BELAJAR MELALUI IDENTIFIKASI GAYA KOGNITIF FIELD DEPENDENT DAN FIELD INDEPENDENT - Fany Adibah; Rudi Antonius (Prodi Pendidikan Bahasa dan Sastra Indonesia IKIP WIDYA DARMA, 2022)
Each individual has various characteristics. Therefore, the way a person behaves, judges, and thinks and learns is also different. The differences that persist in each individual in how to process information and organize it from experiences are called cognitive styles. Some cases that often occur in learning activities are that students find it difficult to understand the subject matter and students are not / less comfortable with the learning experience they get. This of course has an impact on learning outcomes. This paper is a normative library research, which examines and examines books, articles, scientific journals, on optimizing learning outcomes through the identification of field dependent and field independent cognitive styles.